Analisa Dan Evaluasi Kinerja ATS Pada Pelanggan Premium Tegangan Menengah di PT. PLN UP3 Gresik - MOHAMMAD ILHAM; Abdul Ghofar Romdhon; Rini Puji Astutik; Denny Irawan (Journal of Applied Smart Electrical Network and Systems, 2020)
In an effort to meet customer needs on supplying electricity in the industrial era 5.0, it needs to have good services which keep growing up and be innovative. One of them is running a premium service which guarantees better quality of service than that of the regular. This research will discuss all of the obstacles that can disrupt the continuity of electricity supply to the customer with premium services, starting from the disruptions at the supply side until at the installation owned by the customer. From the analysis result, ATS (Automatic Transfer Switch) failed several times on working so that caused a black out at the customer side which it should be avoided. Therefore, it is necessary to make some adjustments on setting and wiring to some problems which may arise so that the potential disruption of the ATS or equipment failure can be suppressed. This research aims to minimize and even eliminate ATS performance failures due to system disturbances by implementing rewiring, adding a permissive interlocking system and adding a PLC with a time delay setting.